AEROFORCASTING ANALYSIS AND PREVISION POSSIBILITIES OF ABUNDANT PRECIPITATION EMERGENCE IN RA (Proceedings of the YSU C: Geological and Geographical Sciences, 2008)
Conditioned by the geographical location of Armenia, the circulation of atmosphere, with the peculiarities of orographical conditions, especially in hot season, the abundant precipitations do harm to various fields of economy. Nowadays the conditions of emergence of precipitation and the drafting of foresight methods are a great problem for synoptical meteorology.
Keywords: aeroforcasting analysis; orographical conditions; circulation of atmosphere